Evaluation of Smear Layer Removal and Antimicrobial Efficacy of Intracanal Herbal Irrigants - Ahmed Ali Alelyani (Journal of Pharmacy and Bioallied Sciences)
Background: The removal of the smear layer and antimicrobial efficacy are critical factors in endodontic treatment. Conventional chemical irrigants like sodium hypochlorite (NaOCl) and ethylenediaminetetraacetic acid (EDTA) have proven effective but can have adverse effects. Materials and Methods: A total of 60 extracted single-rooted human teeth were randomly assigned to four groups of 15 each. Group 1 was irrigated with 5.25% NaOCl, group 2 with 17% EDTA, group 3 with 10% neem extract, and group 4 with 5% turmeric extract. Smear layer removal was assessed using scanning electron microscopy (SEM) at the coronal, middle, and apical thirds of the root canals. Antimicrobial efficacy was tested against Enterococcus faecalis using the agar diffusion method, and the zones of inhibition were measured in millimeters. Results: Neem extract showed an average smear layer removal score of 2.5 (±0.3) compared to 1.8 (±0.2) for NaOCl, 1.9 (±0.3) for EDTA, and 3.2 (±0.4) for turmeric extract. Neem and turmeric extracts demonstrated significant antimicrobial activity with mean inhibition zones of 16 mm (±1.2) and 14 mm (±1.1), respectively, compared to 18 mm (±1.5) for NaOCl and 15 mm (±1.3) for EDTA. Conclusion: Herbal irrigants, particularly neem extract, show promise as effective alternatives to conventional irrigants for smear layer removal and antimicrobial activity. Their biocompatibility and comparable efficacy suggest potential for use in endodontic practice.